Diversity and evolution of the Titanosaurs from the Upper Cretaceous of the Bauru Basin - Silva Junior, Julian Cristian Gonçalves da (2023)
Titanosaurs form the most abundant clade within Sauropoda, also representing the richest group of dinosaurs from the Cretaceous of Brazil. Despite the large number of records, the affinities of the Brazilian species are still poorly resolved. Thus, the studies carried out during this thesis sought a greater understanding of the taxonomic and systematic aspects of these animals. The contributions were divided into four appendices: the first deals with the reassessment of a species of titanosaur from the interior of São Paulo, previously included in the typically Argentine genus Aeolosaurus. After a review of its synapomorphies, a new genus - Arrudatitan - was coined to receive this species. The phylogenetic hypothesis resulting from this study was also used to define new clades in the phylocode. Appendix 2 includes the description of new fossil remains found in Uberaba-MG, which led to the reassessment of two other known species in the region: Baurutitan britoi and Trigonosaurus pricei. The resulting information showed that the individual assigned as a holotype of T. pricei actually represented a specimen of B. britoi. The material assigned as paratype of T. pricei represents a new species, named in this paper as Caieiria allocaudata. In the appendix 3, new specimens of titanosaur teeth are described, also from the region of Uberaba, including the description of the largest titanosaur tooth ever found in the world. The information in this manuscript shows that the region of Uberaba was capable of supporting a wide fauna of titanosaurs, from juvenile animals to giant adult specimens. Finally, appendix 4 presents some materials that are listed in the Museum of Dinosaurs in Uberaba, but that have not yet been formally described, either because of the impossibility of assigning them to already known taxa or the absence of unique characteristics that allow the creation of new species, but which prove to be material with an important comparative value and which can also help research on titanosaurs from other regions.